Between perfection and temptation: tracking lexical expressions of chastity and lust in Old and Middle English saints' lives c.950-c.1250. - Poynton-Smith, Claire Alexandra (Trinity College Dublin. School of English. Discipline of English, 2026)
This thesis analyses Old and Middle English vocabulary expressing the themes of LUST and CHASTITY in saints' lives written in English between c.950 and c.1250. The project combines corpus-linguistic approaches to obtaining lexical data with approaches from Conceptual Metaphor Theory and focused close-readings of individual occurrences within the saints' lives. These are compared to the structure of occurrences in the wider reference corpora for Old and Middle English. The thesis focuses on six key word-families and explores them in depth, providing an overview of the existing lexicographical material on each before delving into analysis structured around two crucial metaphors: LUST IS IMPURITY and CHASTITY IS PURITY. The project examines the diachronic continuities and differences in expression between the material from before and after the Norman Conquest. The study has developed a methodology to work with resources from both periods of the language and literature in tandem. It uses historical thesauruses alongside corpus-linguistic software and searches to capture the highest possible number of forms of each word; something not possible if using traditional literary approaches in isolation. The findings of this study highlight the conceptual continuity of the metaphors LUST IS IMPURITY and CHASTITY IS PURITY in the pre- and post- Conquest saints' lives, even where the exact lexical items involved in these expressions change over the period. This is likely due to the experiential grounding of these metaphors and their consequent accessibility and potential for generating readily understood imagery to convey anxieties about lust and rhetorically encourage chastity. The study identifies and examines key patterns of occurrence which emerge from the material and are especially vivid in the hagiographical texts, providing an insight into cultural attitudes towards LUST and CHASTITY and their rhetorical expression. Additionally, the analysis enabled by this study's period-crossing focus and quantitative and qualitative approach challenges the narrative of an extensive lexical and cultural rupture after the Conquest. This has provided a focused window into the deployment of (im)purity language for moral purposes and offering case-studies across not only Old and Middle English hagiographies, but a range of genres in the wider reference corpora.
APPROVED
Keywords: hagiography; Old English; Middle English; corpus linguistics; vice; virtue; chastity; lust; Aelfric; transitional English; saints' lives